EMPIRICAL ANALYSIS OF AGGLOMERATION ECONOMIES IN THE JAPANESE ASSEMBLY‐TYPE MANUFACTURING INDUSTRY FOR 1985–2000: USING AGGLOMERATION AND COAGGLOMERATION INDICES. Issue 1 (24th January 2014) - Tokunaga, Suminori; Kageyama, Masahiro; Akune, Yuko; Nakamura, Ryohei
<x xml:space="preserve">Abstract</x> This empirical study finds that positive but weak agglomeration economies resulted from the agglomeration of Japan's assembly‐type manufacturing industry during 1985–2000. Estimation results particularly indicate positive externalities from coagglomeration and very slightly increasing returns to scale. Traditional studies conceive of agglomeration economies as being related to localization and urbanization. We, however, estimate a flexible translog production function using four‐digit Standard Industrial Classification industry panel data and Ellison and Glaeser's agglomeration index with the same industry and coagglomeration index with different industry groups. We theoretically obtain appropriate and significant results without the homotheticity restriction.